New approaches to nanoparticle sample fabrication for atom probe tomography - Felfer, Peter; Li, Tong; Eder, K.; Galinski, H.; Magyar, A. P.; Bell, D. C.; Smith, G. D. W.; Kruse, N.; Ringer, S. P.; Cairney, J. M. (Elsevier, 2015)
Due to their unique properties, nano-sized materials such as nanoparticles and nanowires are receiving considerable attention. However, little data is available about their chemical makeup at the atomic scale, especially in three dimensions (3D). Atom probe tomography is able to answer many important questions about these materials if the challenge of producing a suitable sample can be overcome. In order to achieve this, the nanomaterial needs to be positioned within the end of a tip and fixed there so the sample possesses sufficient structural integrity for analysis. Here we provide a detailed description of various techniques that have been used to position nanoparticles on substrates for atom probe analysis. In some of the approaches, this is combined with deposition techniques to incorporate the particles into a solid matrix, and focused ion beam processing is then used to fabricate atom probe samples from this composite. Using these approaches, data has been achieved from 10-20 nm core-shell nanoparticles that were extracted directly from suspension (i.e. with no chemical modification) with a resolution of better than +/- 1 nm. (C) 2015 Elsevier B.V. All rights reserve
Keywords: Atom probe tomography; Nanoparticles; Sample preparation; Focussed ion beam